2012
DOI: 10.1111/j.1365-2133.2012.11200.x
|View full text |Cite
|
Sign up to set email alerts
|

Weather conditions and daylight-mediated photodynamic therapy: protoporphyrin IX-weighted daylight doses measured in six geographical locations

Abstract: Where and when to perform daylight-PDT depends on the PpIX light dose and outdoor temperature. The PpIX light dose was influenced by the geographical location (latitude), weather condition and time of year. The UV index was not more suitable than temperature and weather to predict if the intensity of daylight would be sufficient for daylight-PDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
91
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 16 publications
1
91
1
6
Order By: Relevance
“…One way to deliver very low irradiance PDT is by the use of daylight to activate PpIX. It has been demonstrated that for patients with AKs and in particular field AKs, PDT using daylight can have a similar efficacy to c-PDT, is almost pain free and produces excellent cosmetic results (22)(23)(24)(25)(26)(27)(28)(29)(30). However, it is important to note that in these studies, the efficacy of d-PDT was only followed up over 3-6 months, although with high efficacy rates still apparent at six months (31,32) and this is also typical of the follow-up interval used in most studies of most treatments for AK.…”
Section: Conventional Pdt (C-pdt)mentioning
confidence: 99%
See 2 more Smart Citations
“…One way to deliver very low irradiance PDT is by the use of daylight to activate PpIX. It has been demonstrated that for patients with AKs and in particular field AKs, PDT using daylight can have a similar efficacy to c-PDT, is almost pain free and produces excellent cosmetic results (22)(23)(24)(25)(26)(27)(28)(29)(30). However, it is important to note that in these studies, the efficacy of d-PDT was only followed up over 3-6 months, although with high efficacy rates still apparent at six months (31,32) and this is also typical of the follow-up interval used in most studies of most treatments for AK.…”
Section: Conventional Pdt (C-pdt)mentioning
confidence: 99%
“…Initial efficacy and safety studies of d-PDT with MAL were conducted in Copenhagen (22)(23)(24)(25)(26). Subsequently, studies were conducted in central and southern Europe, Brazil and Australia (27,(29)(30)(31).…”
Section: Clinical Experience With D-pdtmentioning
confidence: 99%
See 1 more Smart Citation
“…Since assuring constant conditions for daylight-PDT is difficult [100], simulated daylight-PDT (SDL-PDT) has been developed. It can be performed in the doctor's office under standardized, constant conditions with the possibility to monitor the patient at all times.…”
Section: Pdt With Natural and Simulated Daylightmentioning
confidence: 99%
“…Wiegell et al recently demonstrated that the light dose required to activate protoporphyrin IX (PpIX) is influenced by latitude, weather conditions, and time of year. 16 To address these important concerns, Spelman et al conducted a meteorological study assessing the suitability of daylight to perform DL-PDT throughout an entire year in eight locations in Australia. 17 This study concluded that DL-PDT can be performed effectively throughout the year as long as weather conditions permit exposure to daylight for 2 hours.…”
Section: Introductionmentioning
confidence: 99%